2019
DOI: 10.3389/fcvm.2019.00025
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils in Post-myocardial Infarction Inflammation: Damage vs. Resolution?

Abstract: Inflammation not only plays a crucial role in acute ischemic cardiac injury, but also contributes to post-infarction repair and remodeling. Traditionally, neutrophils have been merely considered as detrimental in the setting of an acute myocardial infarction. However, recently published studies demonstrated that neutrophils might also play an important role in cardiac repair by regulating reparative processes. An emerging concept is that different neutrophil subsets exist, which might exhibit separate function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
124
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(130 citation statements)
references
References 86 publications
2
124
0
4
Order By: Relevance
“…These cells have been usually considered as pro-inflammatory cells and according to clinical outcomes in myocardial disease, the increase of circulating neutrophils after EV-CDCs administration could be correlated with an aggravated outcome [38]. On the contrary, there are evidences for the pro-regenerative and antiinflammatory capacity of these cells in myocardial infarction [27,39]. Considering this duality, the increase of circulating neutrophils after EV-CDCs treatment deserves further investigation and a full characterization of these neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…These cells have been usually considered as pro-inflammatory cells and according to clinical outcomes in myocardial disease, the increase of circulating neutrophils after EV-CDCs administration could be correlated with an aggravated outcome [38]. On the contrary, there are evidences for the pro-regenerative and antiinflammatory capacity of these cells in myocardial infarction [27,39]. Considering this duality, the increase of circulating neutrophils after EV-CDCs treatment deserves further investigation and a full characterization of these neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study have shown that excessive accumulation of neutrophils exacerbated myocardial infarct size 24 h after permanent occlusion of LCA 33 . In addition, attenuating the recruitment of neutrophils decreased the infarct size in permanent occlusion of LCA and myocardial I/R injury 31,34 . It is implicated that inhibition of neutrophil activation attenuates tissue injury after MI.…”
Section: Discussionmentioning
confidence: 97%
“…Neutrophils infiltrate the infarct area in the first few hours following onset of myocardial ischemia. They produce reactive oxygen species and granule components including myeloperoxidase, thereby exacerbating tissue injury 31 . On the other hand, a recent study has reported that infiltration of neutrophils were required to resolve inflammation post-MI 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the inflammatory, tissue-damaging role that neutrophils have on the acute phase of MIRS, after ≈7 days, the inflammatory Ly6G + CD206neutrophil population is replaced by a Ly6G + CD206 + population that has been described to play an important role in the orchestration of the reparative phase, as reviewed in [70]. Also, apoptotic neutrophils induce an M2 phenotype in infiltrated macrophages upon their phagocytosis, which inhibits the macrophage proinflammatory tissue-damaging response and leads them to produce IL-10 and TGF-β [71,72].…”
Section: Immunoregulation As a Modern Alternative To Immunosuppressionmentioning
confidence: 99%